2018
DOI: 10.3767/persoonia.2018.40.06
|View full text |Cite
|
Sign up to set email alerts
|

Diaporthe diversity and pathogenicity revealed from a broad survey of grapevine diseases in Europe

Abstract: Species of Diaporthe are considered important plant pathogens, saprobes, and endophytes on a wide range of plant hosts. Several species are well-known on grapevines, either as agents of pre- or post-harvest infections, including Phomopsis cane and leaf spot, cane bleaching, swelling arm and trunk cankers. In this study we explore the occurrence, diversity and pathogenicity of Diaporthe spp. associated with Vitis vinifera in major grape production areas of Europe and Israel, focusing on nurseries and vineyards.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
142
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 71 publications
3
142
0
Order By: Relevance
“…Thus, during the past decade, a polyphasic approach, employing multi-locus DNA data together with morphology and ecology, has been employed for species boundaries in the genus (Crous et al 2012, Udayanga et al 2014a, b, Huang et al 2015, Gao et al 2016, 2017, Guarnaccia and Crous 2017, 2018, Hyde et al 2017, 2018, Yang et al 2017a, b, 2018, Guarnaccia et al 2018, Jayawardena et al 2018, Perera et al 2018a, b, Tibpromma et al 2018, Wanasinghe et al 2018). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, during the past decade, a polyphasic approach, employing multi-locus DNA data together with morphology and ecology, has been employed for species boundaries in the genus (Crous et al 2012, Udayanga et al 2014a, b, Huang et al 2015, Gao et al 2016, 2017, Guarnaccia and Crous 2017, 2018, Hyde et al 2017, 2018, Yang et al 2017a, b, 2018, Guarnaccia et al 2018, Jayawardena et al 2018, Perera et al 2018a, b, Tibpromma et al 2018, Wanasinghe et al 2018). …”
Section: Discussionmentioning
confidence: 99%
“…The genus Diaporthe Nitschke represents a cosmopolitan group of fungi occupying diverse ecological behaviour as plant pathogens, endophytes and saprobes (Muralli et al 2006, Rossman et al 2007, Garcia-Reyne et al 2011, Udayanga et al 2011, 2012a, b, 2014a, b, 2015, Gomes et al 2013, Fan et al 2015, Du et al 2016, Dissanayake et al 2017b, Guarnaccia and Crous 2017, Yang et al 2017a, b, 2018, Guarnaccia et al 2018, Marin-Felix et al 2018). Diaporthe species are responsible for diseases on a wide range of plant hosts, including agricultural crops, forest trees and ornamentals, some of which are economically important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on a range of economically important crops such as grapevine (Guarnaccia et al , 2018), sunflower (Thompson et al , 2011), soybean (Santos et al , 2011), and citrus (Guarnaccia and Crous, 2017), have shown that different Diaporthe species can cause the same disease symptoms. PHR of macadamia caused by D .…”
Section: Discussionmentioning
confidence: 99%
“…Many new Diaporthe species have been described in recent years, based on multilocus phylogenetic studies (Gao et al , 2017; Guarnaccia et al , 2018; Long et al , 2019). Unfortunately, it is rare that much new or useful biological information accompanies these newly described taxa.…”
Section: Discussionmentioning
confidence: 99%